2012
DOI: 10.1016/j.wem.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Rare Mitochondrial DNA Polymorphisms are Associated with High Altitude Pulmonary Edema (HAPE) Susceptibility in Han Chinese

Abstract: Background.— The role of genetics in determining an individual's susceptibility to high altitude pulmonary edema (HAPE) is unclear. However a number of genetic polymorphisms have recently been found to be overrepresented in patients with HAPE. Changes at the mitochondrial level may play an important role in the human body's adaptation to hypoxia. Polymorphisms of mitochondrial DNA (mtDNA) have been shown to be responsible for differences in organelle function. Therefore, the frequency of mtDNA 3397A/G and 3552… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
15
1
1
Order By: Relevance
“…Our previous studies showed mitochondrial gene polymorphisms are also involved in the processes of acute impairment and chronic acclimatization of migrating lowlanders, as well as genetic adaptation of native residents at high altitudes 44 . Some individuals with certain mitochondrial DNA variations are susceptible to mountain sicknesses 45 . However, specific tests or biomarkers are sought after which would be more reliable and accessible for early prediction of AMS-S.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed mitochondrial gene polymorphisms are also involved in the processes of acute impairment and chronic acclimatization of migrating lowlanders, as well as genetic adaptation of native residents at high altitudes 44 . Some individuals with certain mitochondrial DNA variations are susceptible to mountain sicknesses 45 . However, specific tests or biomarkers are sought after which would be more reliable and accessible for early prediction of AMS-S.…”
Section: Discussionmentioning
confidence: 99%
“…High altitude Pulmonary Edema (HAPE) is a life threatening, multifactorial complex disease condition which occurs due to rapid ascent to high altitude ~ 3000 m above sea level, where the oxygen content in air is only 60% of that at sea level 7 . Genetic predisposition to the disease is largely unknown, but it would be a function of gene environment interaction 8 . The role of genetics in determining the individual’s susceptibility to HAPE is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also showed that certain mitochondrial haplogroups are predisposed to high-altitude diseases while others can protect against mountain sickness 17,18 . Research on mitochondrial genome shows that haplotype 3010G–3970C is significantly different in frequency between high and low altitude populations suggesting that this haplotype may be responsible for adaptation to low-oxygen environment 19 . Mitochondrial haplogroup N9b is protective against myocardial infarction in Japanese men 20 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 It is believed that the renin-angiotensin-aldosterone system, nitric oxide pathway, and hypoxia-inducible factor pathway, are controlled by genes that differ in HAPE-susceptible patients. 6 Other studies provide evidence of mitochondrial DNA 8 or heat shock protein 9 polymorphisms in HAPE-susceptible individuals or differences within the major histocompatibility complex. 10 Although the genetic connection is not yet clearly established by the research, these and future studies may help to better explain our patient’s risk, protecting his offspring in future generations.…”
Section: Discussionmentioning
confidence: 99%